The Use of Problem Based Learning (PBL) Model to Improve The Motivation in MAN Blangpidie - Samsulimi Samsulimi; Cut Nurmaliah; Safrida Safrida (Universitas Syiah Kuala, 2017)
This study aimed to use the learning model Problem Based Learning in increasing motivation, learning outcomes, and the relationship between motivation and student learning outcomes in the human digestive system concept. This research was conducted in May 2016 at MAN Blangpidie, Aceh Province. This type of research used experimental methods and descriptive with pretest-posttest design One Group Design. The subjects were all students of grade XI MAN Blangpidie totaling 120 students, the sample in this study is 40 students. Data analysis was performed by ARCS questionnaires motivation percentage. The results showed that an increase in student motivation t-hit = 14.61 t-table = 1.99. The conclusion was that the use of Problem Based Learning model of learning can increase student’s motivation in the human digestive systemconcept for class XI MAN Blangpidie